The THE EFFECT OF OUTDOOR LEARNING ON THE EXPLORATORY ABILITY OF CHILDREN AGED 5–6 YEARS - Monica Dian; Nia Fatmawati; Nopiana (Awladuna: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study examines the effect of the outdoor learning method on the exploratory abilities of children aged 5–6 years at Harapan Bangsa Kindergarten, Jati Agung. The purpose of this study is to determine the influence of outdoor learning on early childhood exploratory abilities. This research is quantitative in nature, employing a pre-experimental design with a one-group pretest–posttest design. The data collection technique used was observation, while the data analysis technique employed was the Wilcoxon signed-rank test. Based on the research findings, there is a significant effect on the exploratory abilities of early childhood after the implementation of outdoor learning activities. The results of the Wilcoxon test analysis obtained a Z value of -3.417 with an Asymp. Sig. (2-tailed) value of 0.001, indicating that the probability is below 0.05 (p < 0.05). Thus, Ha is accepted, meaning that there is a significant effect on the exploratory abilities of children aged 5–6 years after the implementation of outdoor learning activities.